2020
DOI: 10.3390/biom10071010
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Insights of Copper Sulfate Exposure-Induced Nephrotoxicity: Involvement of Oxidative and Endoplasmic Reticulum Stress Pathways

Abstract: The precise pathogenic mechanism in Cu exposure-cause nephrotoxicity remains unclear. This study investigated the underlying molecular mechanism of copper sulfate (CuSO4)-induced nephrotoxicity. Mice were treated with CuSO4 at 50, 100, 200 mg/kg/day or co-treated with CuSO4 (200 mg/kg/day) and 4-phenylbutyric acid (4-PBA, 100 mg/kg/day) for 28 consecutive days. HEK293 cells were treated with CuSO4 (400 μM) with or without superoxide dismutase, catalase or 4-PBA for 24 h. Results showed that CuSO4 expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…The previous studies had demonstrated that oxidative stress might play a critical role in CuSO 4 -induced nephrotoxicity in vitro in kidney cell lines (i.e., HEK293 cells) and in vivo in a mouse/rat nephrotoxicity model ( 10 , 23 ). In line with these observations, lower levels of GSH and marked decreases of SOD and CAT activities were detected in the kidney tissues of mice exposed with CuSO 4 ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The previous studies had demonstrated that oxidative stress might play a critical role in CuSO 4 -induced nephrotoxicity in vitro in kidney cell lines (i.e., HEK293 cells) and in vivo in a mouse/rat nephrotoxicity model ( 10 , 23 ). In line with these observations, lower levels of GSH and marked decreases of SOD and CAT activities were detected in the kidney tissues of mice exposed with CuSO 4 ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cu overdose could disturb this balance and induce the production of excessive ROS, which leads to lipid, protein and DNA damage ( 39 ). Previous studies demonstrated that CuSO 4 or copper chloride (CuCl 2 ) exposure can induce the production of excessive ROS in HEK293 cells, mouse liver cells or neuronal cells ( 23 , 40 , 41 ). Mitochondria are not only the major producer of cellular ROS but also a target ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study revealed that CuSO 4 induces cellular ROS production in HEK293 cells. [ 20 ] Administration of CuSO 4 significantly inhibited the effect of a uniform magnetic field on PEI‐mediated transfection (Figure S2B, Supporting Information). To confirm the uniform magnetic field‐dependent enhancement of PEI‐mediated transfection in vivo, eight‐week‐old male mice were transfected with peGFP‐C1 plasmid DNA via tail vein injection and exposed to a 1.6 mT uniform magnetic field for 17 h (Figure S3A‐C, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Similar findings were also reported by Ghanem ( 2006 Several histopathological alterations in the kidney of Tilapia spp. from Lake Qarun were recorded a severe vacuolar degeneration with hypertrophy of epithelial cells at the renal tubules, severe degeneration and necrosis in the renal tubules with focal areas of necrosis between the renal tubules, haemorrhage, haemolysis and aggregations of inflammatory cells between the renal tubules, depletion in the haemopoietic areas, dilation of the tubular lumen, edema in Bowman's capsules with atrophy in the glomeruli as well as dilation and congestion in renal blood vessels Mohamed, 2019;Dai et al, 2020 ).…”
Section: Histopathological Studies: 21 Kidneys Histopathologymentioning
confidence: 99%